Книга, которая учит любить книги даже тех, кто не любит читать - Буше Франсуа (Клевер-Медиа-Групп, 2012)
Экземпляры: Д.О. (20191209) / Инвентарный номер: 43391 / Цена: 288.53 / Сис.шифр: 74.2 / Авт.знак: Б 94 / ББК: 74.202.4